Poetry and perlocution in Psalm 26 - Botha, Phil J. (Old Testament Essays, 2011)
Psalm 26 has been described as a late pre-exilic prayer of innocence. In it a speaker professes innocence, invites Yahweh to put him to the test, and expresses dissociation from certain groups of people who behave unethically. In contrast to this type of behaviour, the speaker expresses a strong desire to visit the temple in order to praise Yahweh among co-believers. This article investigates its poetic and literary features and speech-act potential. Its form and the connections it displays with the work of the post-exilic wisdom editors of Psalms and the Deuteronomistic works are used to argue that it is an argumentative text rather than a liturgical remnant. Its purpose seems to have been to inspire members of the post-exilic in-group of the author to imitate David and Hezekiah in their whole-hearted dedication to Yahweh, since Yahweh would eventually vindicate their uprightness.
free